Isolating membrane and preparation method thereof, secondary battery and electric device

By using a porous base film with a substrate phase and filling phase in the secondary battery, the low thermal stability of the fill phase is used when the temperature is increased to melt the closed pores, which solves the problem that the existing technology cannot terminate the abnormal temperature increase of the secondary battery. , Improved the reliability of the secondary battery.

CN119340607AActive Publication Date: 2025-01-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310889367.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The existing isolation membrane cannot effectively terminate the secondary battery when the temperature rises abnormally.

Method used

A porous base film is used, including a matrix phase and a filling phase dispersed in the matrix phase. The melting peak temperature of the matrix phase is higher than the melting peak temperature of the filling phase, so that when the temperature of the secondary battery increases, the filling phase melts and seals first. pores to terminate electrochemical reactions.

Benefits of technology

Effectively prevent the internal temperature of the secondary battery from continuing to rise to improve the reliability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340607A_ABST
    Figure CN119340607A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, and particularly provides an isolating membrane and a preparation method thereof, a secondary battery and an electric device. The isolating membrane comprises a porous base membrane, the porous base membrane comprises a matrix phase and a filling phase dispersed in the matrix phase, a test curve of a differential scanning calorimeter of the porous base membrane comprises a melting peak of the matrix phase and a melting peak of the filling phase at the same time, and the temperature of the melting peak of the matrix phase is higher than that of the melting peak of the filling phase. The separator provided by the present application can provide reliability of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an isolation membrane and a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features of light weight, no pollution and no memory effect. With the continuous development of the new energy industry, users have put forward higher requirements for the reliability of secondary batteries. However, when the temperature of the secondary battery rises abnormally, the existing isolation film cannot meet the termination of the abnormal temperature. Summary of the invention

[0003] In view of the technical problems existing in the background technology, the present application provides an isolation film and a preparation method thereof, a secondary battery and an electrical device, aiming to solve the termination of the secondary battery due to abnormal temperature conditions.

[0004] In order to solve the above technical problems, the first technical solution adopted in the present application is: to provide an isolation membrane, which includes a porous base membrane, the porous base membrane includes a matrix phase and a filling phase dispersed in the matrix phase, and the test curve of the differential scanning calorimeter of the porous base membrane includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase.

[0005] In the technical solution of the embodiment of the present application, the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase, that is, the matrix phase has better thermal stability than the filling phase. Therefore, when the internal temperature of the secondary battery is high, the filling phase melts first due to its poorer thermal stability, thereby promptly sealing the pores of the isolation membrane, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise, thereby improving the reliability of the secondary battery.

[0006] In any embodiment of the present application, the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is greater than 1, and can be selected from 1.2 to 2.0.

[0007] In the technical solution of the embodiment of the present application, the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is within the above-mentioned range, which can enable sufficient filling phase crystals to be formed in the isolation membrane, thereby facilitating the realization of closed-cell performance; and enables the finished isolation membrane to have good pore-forming performance and high strength.

[0008] In any embodiment of the present application, in the X-ray diffraction pattern of the porous base film, the porous base film has a diffraction peak in the range of 15°<2θ<17°.

[0009] In the technical solution of the embodiment of the present application, the porous base membrane has a diffraction peak in the range of 15°<2θ<17°, and the diffraction peak here is the diffraction peak of the β crystal in the porous base membrane. The higher the β crystal content in the porous base membrane, the higher the overall strength of the porous base membrane.

[0010] In any embodiment of the present application, in the X-ray diffraction pattern of the porous base film, the porous base film has a diffraction peak in the range of 23°<2θ<25°.

[0011] In the technical solution of the embodiment of the present application, the porous base membrane has a diffraction peak in the range of 23°<2θ<25°, where the diffraction peak is the diffraction peak of the α crystal in the porous base membrane. The α crystal in the porous base membrane is conducive to the realization of the thermal closure function.

[0012] In any embodiment of the present application, in the X-ray diffraction pattern of the porous base membrane, the porous base membrane includes a first diffraction peak in the range of 15°<2θ<17°, the porous base membrane includes a second diffraction peak in the range of 23°<2θ<25°, and the diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak.

[0013] In the technical solution of the embodiment of the present application, the porous base membrane includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base membrane includes a second diffraction peak in the range of 23°<2θ<25°. The diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak. The intensity of the first diffraction peak is greater than that of the second diffraction peak, indicating that the β crystal content accounts for more than the α crystal content. Therefore, under the premise that the overall strength of the isolation membrane is large, the thermal closure function of the isolation membrane can be realized, thereby improving the reliability of the isolation membrane.

[0014] In any embodiment of the present application, the filling phase includes α-crystal grains; and the base film phase includes β-crystal grains.

[0015] In the technical solution of the embodiment of the present application, the filling phase of the isolation membrane includes α-crystal grains, and the matrix phase includes β-crystal grains, so that the thermal closure function of the isolation membrane can be achieved while the overall strength of the isolation membrane is high, thereby improving the reliability of the isolation membrane.

[0016] In any embodiment of the present application, the grain size of the filling phase is 0.1 μm-2 μm, and can be optionally 0.1 μm-0.5 μm.

[0017] In the technical solution of the embodiment of the present application, the grain size of the filling phase is controlled within the above-mentioned range. When the internal temperature of the secondary battery is high, the filling phase melts first due to its low melting point, thereby promptly sealing the pores of the isolation membrane, achieving rapid shutdown, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise. At the same time, the isolation membrane has better strength and elongation at break, so that the reliability of the secondary battery is improved.

[0018] In any embodiment of the present application, the mass proportion of the filling phase in the substrate is 10%-40%, and can be optionally 15%-25%.

[0019] In the technical solution of the embodiment of the present application, the mass proportion of the filling phase is controlled within the above range. When the internal temperature of the secondary battery is high, a sufficient amount of the filling phase melts to seal the pores of the isolation membrane to achieve thermal shutdown. At the same time, the matrix phase and the filling phase can balance the physical strength of the isolation membrane and improve the reliability of the secondary battery.

[0020] In any embodiment of the present application, the relative molecular mass of the material of the filling phase is less than or equal to 1.2 million, and can be selected as 400,000-600,000; the relative molecular mass of the material of the matrix phase is greater than or equal to 300,000, and can be selected as 300,000-2.5 million.

[0021] In the technical solution of the embodiment of the present application, the relative molecular weights of the filling phase and the matrix phase are limited to the above range, and the matrix phase and the filling phase can balance the physical strength of the isolation membrane and improve the reliability of the secondary battery.

[0022] In any embodiment of the present application, the temperature of the melting peak of the matrix phase is 160°C-350°C, and can be 160°C-180°C; the temperature of the melting peak of the filling phase is 60°C-180°C, and can be 80°C-130°C.

[0023] In the technical solution of the embodiment of the present application, the temperature of the melting peak of the matrix phase and the temperature of the melting peak of the filling phase are limited to the above range, which can balance the physical strength of the isolation membrane while timely closing the pores of the isolation membrane when the internal temperature of the secondary battery is high, thereby improving the reliability of the secondary battery.

[0024] In any embodiment of the present application, the material of the matrix phase includes at least one of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polyetheretherketone, polyurethane, and polyester; the material of the filling phase includes at least one of polyethylene and polypropylene.

[0025] In the technical solution of the embodiment of the present application, the material of the matrix phase and the filling phase are limited to the above range, which can meet the material requirements of the isolation membrane. When the internal temperature of the secondary battery is high, the filling phase can promptly close the pores of the isolation membrane, thereby improving the reliability of the secondary battery.

[0026] In any embodiment of the present application, the pore size of the porous base membrane is less than or equal to 0.5 μm, and can be optionally 0.02 μm-0.1 μm.

[0027] In the technical solution of the embodiment of the present application, the pore size of the porous base membrane is less than or equal to 0.5 μm, which can effectively block the pores after the filling phase is melted, achieve thermal shutdown, and improve the reliability of the secondary battery.

[0028] In any embodiment of the present application, the isolation film satisfies at least one of the following (1)-(9):

[0029] (1) The closed-cell temperature of the isolation film is 120°C-170°C, and can be optionally 120°C-130°C;

[0030] (2) The closing time of the isolation membrane is less than or equal to 10s, and can be selected as 5s-10s;

[0031] (3) The transverse elongation at break of the separator is ≥ 100%, which can be 100%-120%;

[0032] (4) The longitudinal elongation at break of the separator is ≥ 60%, which can be 60%-80%;

[0033] (5) Transverse tensile strength of the separator ≥ 1500kgf / cm 2 , optional 2000kgf / cm 2 -4000 kgf / cm 2 ;

[0034] (6) The longitudinal tensile strength of the separator is ≥ 2000kgf / cm 2 , optional 2000gf / cm 2 -4000 kgf / cm 2 ;

[0035] (7) The puncture strength of the isolation film is ≥60gf, which can be selected as 120gf-420gf;

[0036] (8) The porosity of the isolation membrane is 30%-90%, and can be optionally 30%-50%;

[0037] (9) The air permeability of the isolation film is less than or equal to 300 sec / 100 cc, and can be selected from 100 sec / 100 cc to 300 sec / 100 cc.

[0038] In the technical solution of the embodiment of the present application, the isolation film satisfies at least one of the above conditions.

[0039] It can effectively improve the ductility of the isolation membrane, enhance the puncture performance of the isolation membrane, and quickly respond to thermal anomalies to achieve thermal shutdown, thereby further improving the reliability of the secondary battery.

[0040] The second technical solution adopted in the present application is to provide a method for preparing the isolation membrane as described above. The preparation method includes: mixing the raw materials for forming the matrix phase, the raw materials for forming the filling phase and the nucleating agent to form a precursor, wherein the crystallization temperature of the raw materials for forming the filling phase is lower than the crystallization temperature of the raw materials for forming the matrix phase; extruding the precursor to form a first intermediate product; casting the first intermediate product to form a second intermediate product, wherein the casting process includes a first temperature stage and a second temperature stage, and the casting temperature of the first temperature stage is higher than the casting temperature of the second temperature stage; and stretching the second intermediate product to obtain a porous base film. The porous base film includes a matrix phase and a filling phase dispersed in the matrix phase, and the test curve of the differential scanning calorimeter of the porous base film includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase.

[0041] In the technical scheme of the embodiment of the present application, the raw materials for forming the matrix phase, the raw materials for forming the filling phase and the nucleating agent are mixed, wherein the crystallization temperature of the raw materials for the filling phase is lower than the crystallization temperature of the raw materials for forming the matrix phase. In the casting process, a casting process is adopted in which the casting temperature of the first temperature stage is higher than the casting temperature of the second temperature stage, so that the raw materials for the matrix phase crystallize first and the raw materials for the filling phase crystallize later. The filling phase is dispersed in the matrix phase and then stretched to form a porous isolation membrane. The temperature of the melting peak of the matrix phase of the isolation membrane is higher than the temperature of the melting peak of the filling phase. The matrix phase has better thermal stability than the filling phase. Therefore, when the internal temperature of the secondary battery is high, the filling phase melts first due to its poor thermal stability, thereby timely sealing the pores of the isolation membrane, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise, thereby improving the reliability of the secondary battery.

[0042] In any embodiment of the present application, the melt index of the filling phase raw material is greater than the melt index of the matrix phase raw material; optionally, the ratio of the melt index of the filling phase raw material to the melt index of the matrix phase raw material is equal to 1.1-10.1, and can be optionally 1.1-2.1.

[0043] In the technical solution of the embodiment of the present application, the melting index of the filling phase raw material is greater than the melting index of the matrix phase raw material, and the ratio of the two is limited to the above range. The matrix phase has better thermal stability than the filling phase. When the internal temperature of the secondary battery is high, the filling phase melts first, and then the pores of the isolation membrane are closed in time, terminating the electrochemical reaction, preventing the internal temperature of the secondary battery from continuing to rise, and the reliability of the secondary battery is improved.

[0044] In any embodiment of the present application, the crystallization temperature of the filling phase raw material is 80°C-120°C, optionally 80°C-100°C; and / or, the crystallization temperature of the matrix phase raw material is 125°C-135°C, optionally 125°C-130°C.

[0045] In the technical solution of the embodiment of the present application, the crystallization temperature of the filling phase raw material and the crystallization temperature of the matrix phase raw material are limited to the above-mentioned range, so that the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase. When the internal temperature of the secondary battery is high, the filling phase melts first, and then the pores of the isolation membrane are sealed in time, terminating the electrochemical reaction, preventing the internal temperature of the secondary battery from continuing to rise, and the reliability of the secondary battery is improved.

[0046] In any embodiment of the present application, the casting temperature in the first temperature stage is 125°C-135°C, optionally 125°C-130°C; and / or, the casting temperature in the second temperature stage is 105°C-125°C, optionally 105°C-110°C; and / or, the difference between the casting temperature in the first temperature stage and the casting temperature in the second temperature stage is 10°C-20°C.

[0047] In the technical solution of the embodiment of the present application, limiting the casting temperature within the above range can enable the isolation film to fully crystallize to form a filling phase and a matrix phase.

[0048] In any embodiment of the present application, in the step of stretching the second intermediate product, the transverse stretching temperature is 110°C-120°C, optionally 110°C-115°C; and / or, the longitudinal stretching temperature is 85°C-120°C, optionally 110°C-120°C.

[0049] In the technical solution of the embodiment of the present application, the transverse stretching temperature and the longitudinal stretching temperature are limited to the above ranges, so that the formed isolation film has better physical and chemical properties.

[0050] The third technical solution adopted by the present application is to provide a secondary battery, which includes the above-mentioned separator or the separator prepared by the above-mentioned separator preparation method. The secondary battery includes a positive electrode sheet and a negative electrode sheet, and the separator is arranged between the positive electrode sheet and the negative electrode sheet.

[0051] The fourth technical solution adopted in the present application is: to provide an electrical device, including the secondary battery as described above.

[0052] In the technical solution of the embodiment of the present application, the electrical device includes the above-mentioned secondary battery, and thus has the same advantage of good fast charging performance.

[0053] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0055] Figure 1 is a SEM image of an embodiment of the isolation membrane provided in the present application.

[0056] Figure 2 yes Figure 1 The melting curve of the isolation film is shown.

[0057] Figure 3 It is a schematic diagram of one embodiment of the secondary battery provided in the present application.

[0058] Figure 4 yes Figure 3 Exploded diagram of .

[0059] Figure 5 It is a schematic diagram of an embodiment of a battery module provided in the present application.

[0060] Figure 6 It is a schematic diagram of an embodiment of the battery pack provided in the present application.

[0061] Figure 7 yes Figure 6 Exploded diagram of .

[0062] Figure 8 Schematic diagram of an embodiment of a device in which a secondary battery provided in the present application is used as a power source. DETAILED DESCRIPTION

[0063] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0064] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0065] In the description herein, unless otherwise specified, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0066] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.

[0067] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0068] [Secondary battery]

[0069] A secondary battery is a battery that can be used continuously by recharging the active materials after the battery is discharged. Usually, a secondary battery includes a battery cell (positive electrode, negative electrode, separator), electrolyte and shell. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode to play an isolating role. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode.

[0070] [Isolation film]

[0071] like Figure 1 and Figure 2 As shown, Figure 1 is a SEM image of an embodiment of the isolation film, Figure 2 yes Figure 1The insulating film provided in the embodiment of the present application comprises a porous base film, the porous base film comprises a matrix phase and a filling phase dispersed in the matrix phase, and the test curve of the differential scanning calorimeter of the porous base film includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase.

[0072] Differential Scanning Calorimeter (DSC) can be used to measure the curing reaction temperature and thermal effect of polymer materials, the phase change temperature and thermal effect of materials, the crystallization of polymer materials, the melting temperature and thermal effect of polymer materials, the glass transition temperature of polymer materials, etc. The melting peak reflects the melting process of the material, that is, when the temperature rises to a certain level, the solid material melts into a liquid material, and a certain amount of heat is released. The temperature of the melting peak can be used to evaluate the thermal stability of the material. Thermal stability refers to the stability of the material at high temperature. If the melting peak temperature of the material is high, it means that the material is not easy to melt at high temperature and has good thermal stability; if the melting peak temperature of the material is low, it means that the material is easy to melt at high temperature and has poor thermal stability. In other words, the temperature of the melting peak can also be understood as the melting point, that is, the melting point of the matrix phase is higher than the melting point of the filling phase. In the embodiments of the present application, the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase, that is, the matrix phase has better thermal stability than the filling phase. Therefore, when the internal temperature of the secondary battery is high, the filling phase melts first due to its poorer thermal stability, thereby promptly sealing the pores of the isolation membrane, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise, thereby improving the reliability of the secondary battery.

[0073] In some embodiments, the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is greater than 1, and can be selected as 1.2-2.0. For example, the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase can be 1, 1.1, 1.2, 1.3, 1.4, 1.6, 1.8, 2.0, 2.2, 2.5, 2.8, 3.2, 4, etc., or a range consisting of any two of the above values, for example, 1-1.2, 1.1-1.4, 1.3-1.8, 1.6-2.2, 2.2-2.8, 2.8-4, etc. The melting peak area of ​​the X-ray diffraction spectrum indicates the crystal content, and the larger the area, the higher the crystal content. The peak area ratio indicates the proportion of different crystals in the isolation membrane. The peak area ratio of the melting peak of the matrix phase to the melting peak of the filling phase is within the above range, which can form enough filling phase crystals in the isolation membrane, which is beneficial to the realization of closed-cell performance; and makes the finished isolation membrane have good pore-forming performance and high strength.

[0074] In some embodiments, in the X-ray diffraction pattern of the porous base film, the porous base film has a diffraction peak in the range of 15°<2θ<17°. The physical phenomenon of coherent scattering of X-rays irradiated on a crystal is called diffraction. The diffraction angle of light refers to the angle at which the light path changes when the light is diffracted. For example, in an X-ray diffractometer, 2θ is the diffraction angle, and 2θ is the angle at which the X-ray changes direction after diffraction. The diffraction peak of the porous base film in the range of 15°<2θ<17° is the diffraction peak of the β crystal form, and the β crystal form is a matrix phase crystal. The β crystal form refers to a type of crystal structure of a substance in the solid state. The β crystal form refers to a face-centered cubic crystal system, which belongs to the hexagonal crystal system. The higher the β crystal content, the higher the overall strength of the porous base film. The porous base film has a diffraction peak in the range of 15°<2θ<17°, which can make the isolation membrane have sufficient strength.

[0075] In some embodiments, in the X-ray diffraction pattern of the porous base membrane, the porous base membrane has a diffraction peak in the range of 23°<2θ<25°. The diffraction peak of the porous base membrane in the range of 23°<2θ<25° is the diffraction peak of the α crystal form, and the α crystal form is the filling phase crystallization. The α crystal form refers to another type of crystal structure of a substance in the solid state. The α crystal form generally refers to the body-centered cubic crystal system, which belongs to the monoclinic crystal system. The higher the α crystal content, the more conducive the filling phase crystallization is to realize the thermal pore closing function of the isolation membrane. The porous base membrane has a diffraction peak in the range of 23°<2θ<25°, which is conducive to the realization of the thermal pore closing function of the isolation membrane.

[0076] In some embodiments, in the X-ray diffraction spectrum of the porous base film, the porous base film includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base film includes a second diffraction peak in the range of 23°<2θ<25°, and the diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak. The intensity of the diffraction peak depends on the properties such as the type, content, and relative position of the atoms; the position and intensity of the diffraction peak can reflect the characteristics of the crystal structure, thus becoming the basis for distinguishing the physical phase. The intensity of the diffraction line of each physical phase increases with the increase of its phase content. As mentioned above, the diffraction peak of the porous base film in the range of 15°<2θ<17° is the diffraction peak of the β crystal form. The higher the β crystal content, the higher the overall strength of the porous base film. The diffraction peak of the porous base film in the range of 23°<2θ<25° is the diffraction peak of the α crystal form, and the α crystal form is the filling phase crystallization, so that the filling phase crystallization is conducive to realizing the thermal closure function of the isolation membrane. The porous base membrane includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base membrane includes a second diffraction peak in the range of 23°<2θ<25°. The diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak, indicating that the β-crystal content of the matrix phase is greater than the α-crystal content of the filling phase. Therefore, under the premise of high overall strength of the isolation membrane, the thermal closure function of the isolation membrane can be achieved, thereby improving the reliability of the isolation membrane.

[0077] In some embodiments, the filling phase includes α-crystal grains; the matrix phase includes β-crystal grains. As mentioned above, the higher the α-crystal content, the more conducive the crystallization of the filling phase is to achieving the thermal pore-closing function of the isolation membrane. The higher the β-crystal content, the higher the overall strength of the porous base membrane. Therefore, the filling phase includes α-crystal grains; the matrix phase includes β-crystal grains, which enables the thermal pore-closing function of the isolation membrane to be achieved under the premise of high overall strength of the isolation membrane, thereby improving the reliability of the isolation membrane.

[0078] In some embodiments, the grain size of the filling phase is 0.1 μm-2 μm, and can be 0.1 μm-0.5 μm. For example, the grain size can be 0.1 μm, 0.15 μm, 0.25 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.2 μm, 1.4 μm, 1.7 μm, 2 μm, etc., or a range consisting of any two of the above values, for example, 0.1 μm-0.15 μm, 0.15 μm-0.3 μm, 0.25 μm-0.4 μm, 0.4 μm-0.5 μm, 0.5 μm-0.9 μm, 0.7 μm-1.4 μm, 1.4 μm-2 μm, etc. Generally speaking, the larger the grain size of the polymer crystal, the higher the melting point. Therefore, controlling the grain size of the filling phase within the above range can control the melting point of the filling phase. When the internal temperature of the secondary battery is high, the filling phase melts first due to its low melting point, achieving rapid shutdown, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise. At the same time, the isolation membrane has better strength and elongation at break, so that the reliability of the secondary battery is improved.

[0079] In some embodiments, the mass proportion of the filling phase in the substrate is 10%-40%, and can be 15%-25%. For example, the mass proportion of the filling phase in the substrate can be 10%, 12%, 15%, 18%, 20%, 22%, 24%, 25%, 28%, 30%, 35%, 38%, 40%, etc., or a range composed of any two of the above values, for example, it can be 10%-15%, 12%-18%, 15%-22%, 18%-25%, 25%-30%, 35%-38%, 38%-40%, etc. When the mass proportion of the filling phase is too low, when the internal temperature of the secondary battery is high, the amount of the melted filling phase is too small to seal the pores of the isolation membrane. When the mass proportion of the filling phase is too high, the physical strength of the isolation membrane cannot be maintained. Therefore, the mass proportion of the filling phase is controlled within the above range. When the internal temperature of the secondary battery is high, a sufficient amount of the filling phase melts to seal the pores of the isolation membrane to achieve thermal shutdown. At the same time, the matrix phase and the filling phase can balance the physical strength of the isolation membrane, thereby improving the reliability of the secondary battery.

[0080] In some embodiments, the relative molecular mass of the material of the filling phase is less than or equal to 1.2 million, and can be selected as 400,000-600,000; the relative molecular mass of the material of the matrix phase is greater than or equal to 300,000, and can be selected as 300,000-2.5 million. The relative molecular mass of the material of the filling phase can be 200,000, 300,000, 400,000, 450,000, 480,000, 500,000, 550,000, 600,000, 700,000, 800,000, 900,000, 1 million, 1.1 million, 1.2 million, etc., or a range formed by any two of the above values, for example, 200,000-300,000, 300,000-450,000, 450,000-500,000, 500,000-600,000, 600,000-800,000, 800,000-1 million, 1 million-1.2 million, etc. The relative molecular mass of the material of the matrix phase can be 300,000, 500,000, 600,000, 750,000, 860,000, 1 million, 1.2 million, 1.4 million, 1.65 million, 1.9 million, 2.2 million, 2.5 million, 3 million, 4 million, etc., or a range formed by any two of the above values, for example, it can be 300,000-600,000, 500,000-750,000, 600,000-1 million, 860,000-1.4 million, 1.2 million-1.9 million, 1.65 million-2.2 million, 1.9 million-2.5 million, 2.5 million-4 million, etc.

[0081] The relative molecular mass of the isolation membrane has a well-known meaning in the art, and can be tested using equipment and methods known in the art, for example, using a high-temperature GPC test (differential refractive index detector) for testing.

[0082] The filling phase with a small relative molecular mass has a stronger crystallization ability and is easier to be stably dispersed in the matrix phase with a large relative molecular mass, thereby reducing the sensitivity of the filling phase to high temperature. That is, after the filling phase is heated up, it takes a certain amount of time to conduct heat to the inside of the matrix phase. The matrix phase has a larger relative molecular mass and is more heat-resistant, and the heat transfer is slower, so a higher temperature (i.e., the closed-cell temperature) is required to melt the filling phase and close the pores. The closed-cell temperature refers to the temperature at which the pores of the isolation membrane are closed. The filling phase with a small relative molecular mass can make the closed-cell temperature of the isolation membrane higher. In other words, when the temperature of the secondary battery abnormally rises to a certain temperature, the filling phase with a small relative molecular mass melts to close the pores of the isolation membrane. By limiting the relative molecular masses of the filling phase and the matrix phase to the above range, the matrix phase and the filling phase can balance the physical strength of the isolation membrane and improve the reliability of the secondary battery.

[0083] In some embodiments, the temperature of the melting peak of the matrix phase is 160°C-350°C, and can be 160°C-180°C; the temperature of the melting peak of the filling phase is 60°C-180°C, and can be 80°C-130°C. The temperature of the melting peak of the matrix phase can be 160°C, 165°C, 170°C, 175°C, 180°C, 200°C, 250°C, 300°C, 350°C, etc., or a range consisting of any two of the above values, for example, 160°C-170°C, 170°C-175°C, 175°C-200°C, 200°C-300°C, 250°C-350°C, etc. The temperature of the melting peak of the filling phase may be 60°C, 65°C, 70°C, 75°C, 80°C, 100°C, 110°C, 120°C, 140°C, 160°C, 180°C, etc., or a range formed by any two of the above values, for example, 60°C-70°C, 70°C-80°C, 75°C-110°C, 100°C-140°C, 120°C-160°C, 140°C-180°C, etc. The temperature of the melting peak of the matrix phase and the temperature of the melting peak of the filling phase are limited to the above range, which can balance the physical strength of the isolation membrane and timely close the pores of the isolation membrane when the internal temperature of the secondary battery is high, thereby improving the reliability of the secondary battery.

[0084] In some embodiments, the material of the matrix phase includes at least one of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polyetheretherketone, polyurethane, and polyester; the material of the filling phase includes at least one of polyethylene and polypropylene. For example, in some embodiments, the material of the matrix phase includes polytetrafluoroethylene, and the material of the filling phase includes polyethylene. Wherein, the porous base film includes a first diffraction peak and a second diffraction peak in the range of 15°<2θ<17°, the first diffraction peak corresponds to polytetrafluoroethylene, the second diffraction peak corresponds to polyethylene, and the diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak. For example, in some embodiments, the material of the matrix phase includes polypropylene, and the material of the filling phase includes polyethylene. Wherein, the porous base film includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base film includes a second diffraction peak in the range of 23°<2θ<25°, the first diffraction peak corresponds to polypropylene, and the second diffraction peak corresponds to polyethylene. The diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak. Limiting the materials of the matrix phase and the filling phase to the above range can meet the material requirements of the isolation membrane. When the internal temperature of the secondary battery is high, the filling phase can promptly seal the pores of the isolation membrane, thereby improving the reliability of the secondary battery.

[0085] In some embodiments, the pore size of the porous base membrane is less than or equal to 0.5 μm, and can be selected as 0.02 μm-0.1 μm. For example, the pore size of the porous base membrane can be 0.01 μm, 0.02 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.5 μm, etc., or a range composed of any two of the above values, for example, 0.01 μm-0.04 μm, 0.02 μm-0.06 μm, 0.04 μm-0.1 μm, 0.08 μm-0.3 μm, 0.1 μm-0.35 μm, 0.3 μm-0.5 μm, etc. When the pore size of the porous base membrane is too large, it is easy to cause pore blockage when the active material particles pass through. The pore size of the porous base membrane is less than or equal to 0.5 μm, which can effectively block the pores after the filling phase is melted, achieve thermal shutdown, and improve the reliability of the secondary battery.

[0086] In some embodiments, the isolation film satisfies at least one of the following (1)-(9):

[0087] (1) The closed-cell temperature of the isolation film is 120°C-170°C, and can be optionally 120°C-130°C;

[0088] (2) The closing time of the isolation membrane is less than or equal to 10s, and can be selected as 5s-10s;

[0089] (3) The transverse elongation at break of the separator is ≥ 100%, which can be 100%-120%;

[0090] (4) The longitudinal elongation at break of the separator is ≥ 60%, which can be 60%-80%;

[0091] (5) Transverse tensile strength of the separator ≥ 1500kgf / cm 2 , optional 2000kgf / cm 2 -4000 kgf / cm 2 ;

[0092] (6) The longitudinal tensile strength of the separator is ≥ 2000kgf / cm 2 , optional 2000gf / cm 2 -4000 kgf / cm 2 ;

[0093] (7) The puncture strength of the isolation film is ≥60gf, which can be selected as 120gf-420gf;

[0094] (8) The porosity of the isolation membrane is 30%-90%, and can be optionally 30%-50%;

[0095] (9) The air permeability of the isolation film is less than or equal to 300 sec / 100 cc, and can be selected from 100 sec / 100 cc to 300 sec / 100 cc.

[0096] In some embodiments, the closed-cell temperature of the isolation membrane is 120°C-170°C, and can be 120°C-130°C; the closed-cell time of the isolation membrane is less than or equal to 10s, and can be 5s-10s. For example, the closed-cell temperature of the isolation membrane can be 120°C, 124°C, 130°C, 132°C, 140°C, 146°C, 150°C, 158°C, 163°C, 170°C, etc., or a range consisting of any two of the above values, such as 120°C-130°C, 124°C-140°C, 140°C-150°C, 146°C-158°C, 150°C-170°C, etc. The closed-cell time of the isolation membrane can be 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, etc., or a range consisting of any two of the above values, such as 3s-5s, 4s-7s, 5s-8s, 7s-10s, etc. If the pore closing temperature of the separator is too high and the pore closing time is too long, it means that the filling phase in the separator needs to reach a certain temperature and time before the pores of the separator can be closed in time. If the pore closing temperature of the separator is too low and the pore closing time is too short, the filling phase in the separator will close immediately at a lower temperature. If the pore closing temperature and pore closing time of the separator are within the above range, it can quickly respond to thermal anomalies to achieve thermal shutdown and improve the reliability of the secondary battery.

[0097] The transverse tensile strength (MD), longitudinal tensile strength (TD), transverse elongation at break, and longitudinal elongation at break of the separator all have well-known meanings in the art and can be measured using methods known in the art. For example, they can all be tested with reference to standard GB / T 36363-2018.

[0098] The puncture strength of the isolation membrane has a well-known meaning in the art, and can be tested using equipment and methods known in the art. For example, the puncture strength can be tested according to the standard: GB / T 10004-2008. Specifically, the sample to be tested can be cut into strips, wherein the width of the strip sample is 100 mm. A test piece with a width of 100 mm is mounted on the sample film fixing clamp ring, and then a steel needle with a diameter of 1.0 mm and a top radius of 0.5 mm is used to puncture at a speed of (50±5) mm / min, and the maximum load of the steel needle penetrating the test piece is read. Usually, 5 parallel test samples can be taken at the same time, and 3 points are measured for each test sample, and the arithmetic mean is taken as the final puncture strength.

[0099] According to some embodiments, porosity is a well-known meaning in the art and can be tested using known equipment and methods. For example, the test can be performed with reference to GB / T 24586-2009. The test method is as follows: punch the isolation film or substrate into small disc samples with a diameter of 14 mm, test the thickness, and calculate the apparent volume V1 of the isolation film or substrate according to the cylinder volume calculation formula; refer to GB / T 24586-2009, use an inert gas such as helium or nitrogen as a medium, adopt a gas replacement method, and use a true density tester to measure the true volume V2 of the isolation film or substrate. Then the porosity of the isolation film or substrate = (V1-V2) / V1×100%. The testing instrument can be the AccuPyc II 1340 fully automatic true density tester from Micromeritics, USA.

[0100] According to some embodiments, the air permeability of the isolation film can be tested using equipment and methods known in the art. For example, the air permeability of the isolation film can be tested using the ASTM (Standard Test Method for Resistance of Nonporous Paper to Passage of Air) method. The porosity can be tested using equipment and methods known in the art.

[0101] The separator satisfies at least one of the above (1)-(7), which can effectively improve the ductility of the separator and the puncture performance of the separator, thereby further improving the reliability of the secondary battery.

[0102] The second technical solution adopted by the present application is to provide a method for preparing the isolation membrane as described above. The preparation method comprises the following steps:

[0103] S100: Mixing a raw material for forming a matrix phase, a raw material for forming a filling phase, and a nucleating agent to form a precursor, wherein the crystallization temperature of the raw material for forming the filling phase is lower than the crystallization temperature of the raw material for forming the matrix phase.

[0104] The raw material for forming the matrix phase includes at least one of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polyetheretherketone, polyurethane, and polyester; the raw material for forming the filling phase includes at least one of polyethylene and polypropylene. For example, in some embodiments, the material of the matrix phase includes polypropylene, and the material of the filling phase includes polyethylene.

[0105] The nucleating agent may include an α-crystal nucleating agent. The α-crystal nucleating agent is not particularly limited, and various α-crystal nucleating agents known in the art can be used. One or more α-crystal nucleating agents can be used alone or in combination.

[0106] The α-crystal nucleating agent includes an inorganic α-crystal nucleating agent and an organic α-crystal nucleating agent.

[0107] Inorganic α-crystal nucleating agents mainly include talc, calcium oxide, carbon black, calcium carbonate, mica, inorganic pigments, kaolin and catalyst residues.

[0108] The organic α-crystal nucleating agent may include at least one of an aromatic acid metal soap α-nucleating agent, a sorbitol α-nucleating agent, a rosin α-nucleating agent, and an organic phosphate α-nucleating agent.

[0109] Aromatic acid metal soap alpha nucleating agents may include at least one of the metal salts of aromatic carboxylic acids sodium benzoate, aluminum benzoate, and aluminum p-tert-butylbenzoate. Sorbitol alpha nucleating agents may include at least one of dibenzylidene sorbitol, substituted dibenzylidene sorbitol, 1,3:2,4-di-p-methylbenzylidene sorbitol, and di-(3,4-dimethyldibenzylidene) sorbitol. Rosin alpha nucleating agents may include at least one of dehydroabietic acid, abietic acid salt, a mixture of abietic acid and its salts, and abietic amide. Organic phosphate alpha nucleating agents may include at least one of organic phosphate esters, organic phosphate basic metal salts, and composites.

[0110] The nucleating agent may include a β-crystal nucleating agent. There is no particular limitation on the β-crystal nucleating agent, and various known β-crystal nucleating agents can be used. One or more β-crystal nucleating agents can be used in combination.

[0111] β-crystal nucleating agents include inorganic oxide β-nucleating agents, inorganic salt β-nucleating agents, condensed ring aromatic hydrocarbon β-nucleating agents, organic carboxylic acids and their salts β-nucleating agents, aromatic amide β-nucleating agents and rare earth β-nucleating agents.

[0112] The inorganic oxide β-nucleating agent may include at least one of an oxide of a metal of Group IIA of the periodic table and aluminum trioxide. The inorganic salt β-nucleating agent may include at least one of calcium silicate, calcium carbonate, and calcium sulfate. The condensed ring aromatic hydrocarbon β-nucleating agent may include at least one of quinacridone quinone, triphenothiazine, and disazo yellow. The organic carboxylic acid β-nucleating agent may include at least one of adipic acid dibenzoyl hydrazide and suberic acid. The organic carboxylate β-nucleating agent may include at least one of calcium tetrahydrophthalate, calcium suberate, calcium pimelate, polycarboxylic acid calcium salt, and polycarboxylic acid zinc salt. The aromatic amide β-nucleating agent may include at least one of 2,6-phthalic acid cyclohexylamide, 2,6-naphthalene dicarboxylic acid cyclohexylamide, and aromatic dicarboxamide. The rare earth β-nucleating agent may include at least one of a rare earth lanthanide mononuclear metal compound, a rare earth multi-complex, and a binuclear complex formed by a rare earth and a Group IIA metal.

[0113] Nucleating agents are used to form the crystal form of the matrix phase. The higher the crystallization temperature, the easier it is to crystallize first. The crystallization temperature of the raw material forming the filling phase is lower than the crystallization temperature of the raw material forming the matrix phase, so that the filling phase crystallizes first before the matrix phase.

[0114] S200: Extruding the precursor to form a first intermediate product.

[0115] S300: performing a casting process on the first intermediate product to form a second intermediate product.

[0116] The casting treatment includes a first temperature stage and a second temperature stage, and the casting temperature in the first temperature stage is higher than the casting temperature in the second temperature stage.

[0117] S400: performing a stretching process on the second intermediate product.

[0118] In the technical scheme of the embodiment of the present application, the raw material for forming the matrix phase, the raw material for forming the filling phase and the nucleating agent are mixed, wherein the crystallization temperature of the raw material of the filling phase is lower than the crystallization temperature of the raw material for forming the matrix phase. In the usual casting process, only one temperature treatment will form homogeneous crystals, thereby showing only one melting peak. In the casting process provided in the embodiment of the present application, a casting process in which the casting temperature of the first temperature stage is higher than the casting temperature of the second temperature stage is adopted, so that the raw material of the matrix phase crystallizes first and the raw material of the filling phase crystallizes later, and the filling phase is dispersed in the matrix phase, thereby showing two melting peaks. After stretching treatment, a porous isolation membrane is formed, wherein the temperature of the melting peak of the matrix phase of the isolation membrane is higher than the temperature of the melting peak of the filling phase, and the matrix phase has better thermal stability than the filling phase. Therefore, when the internal temperature of the secondary battery is high, the filling phase melts first due to poorer thermal stability, and then the pores of the isolation membrane are closed in time, the electrochemical reaction is terminated, and the internal temperature of the secondary battery is prevented from continuing to rise, and the reliability of the secondary battery is improved.

[0119] In some embodiments, the melt index of the filler phase raw material is greater than the melt index of the matrix phase raw material, and the ratio of the two is 1.1-10.1, and can be 1.1-2.1. For example, the ratio of the melt index of the filler phase raw material to the melt index of the matrix phase raw material is 1.1, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, etc., or a range consisting of any two of the above values, such as 1.1-1.5, 1.4-1.6, 1.5-1.8, 1.7-2.0, 1.9-2.1, etc. Melt index is a value that indicates the fluidity of plastic materials during processing. It was developed by the American Measurement Standards Association (ASTM) based on the method used by DuPont to identify plastic properties. The test method is: first melt the plastic pellets into plastic fluid, and then measure its grams (g) after it flows out through a 2.1mm diameter tube within a certain time (10 minutes), at a certain temperature and pressure (different standards for various materials). The larger the value, the better the processing fluidity of the plastic material, and vice versa. The melt index of the filling phase raw material is greater than the melt index of the matrix phase raw material, and the ratio of the two is limited to the above range. The matrix phase has better thermal stability than the filling phase. When the internal temperature of the secondary battery is high, the filling phase melts first, and then the pores of the isolation membrane are closed in time, terminating the electrochemical reaction, preventing the internal temperature of the secondary battery from continuing to rise, and the reliability of the secondary battery is improved.

[0120] In some embodiments, the crystallization temperature of the filling phase raw material is 80°C-120°C, and can be 80°C-100°C; the crystallization temperature of the matrix phase raw material is 125°C-135°C, and can be 125°C-130°C. The crystallization temperature of the filling phase raw material and the crystallization temperature of the matrix phase raw material are limited to the above range, so that the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase. When the internal temperature of the secondary battery is high, the filling phase melts first, and then the pores of the isolation membrane are closed in time, the electrochemical reaction is terminated, and the internal temperature of the secondary battery is prevented from continuing to rise, and the reliability of the secondary battery is improved.

[0121] In some embodiments, the temperature of the casting sheet in the first temperature stage is 125°C-135°C, and can be 125°C-130°C; the temperature of the casting sheet in the second temperature stage is 105°C-125°C, and can be 105°C-110°C; optionally, the difference between the temperature of the casting sheet in the first temperature stage and the temperature of the casting sheet in the second temperature stage is 10°C-20°C. For example, in some embodiments, the temperature of the casting sheet in the first temperature stage can be 125°C, 126°C, 128°C, 130°C, 131°C, 133°C, 135°C, etc., or a range composed of any of the above values, for example, 125°C-126°C, 126°C-130°C, 130°C-133°C, 133°C-135°C, etc. In some embodiments, the casting temperature of the second temperature stage can be 105°C, 108°C, 110°C, 115°C, 118°C, 120°C, 122°C, 125°C, etc., or a range consisting of any of the above values, for example, 105°C-110°C, 108°C-115°C, 115°C-120°C, 120°C-125°C, etc. In some embodiments, the difference between the casting temperature of the first temperature stage and the casting temperature of the second temperature stage is 10°C, 12°C, 14°C, 16°C, 18°C, 20°C, or a range consisting of any of the above values, for example, 10°C-12°C, 12°C-16°C, 16°C-20°C, etc. The crystallization temperature of the filling phase is higher, and the first temperature stage preferentially crystallizes and separates from the matrix phase, while in the second temperature stage, the matrix phase has the largest crystallization rate and is fully crystallized. Limiting the casting temperature to the above range can enable the isolation film to fully crystallize to form the filling phase and the matrix phase.

[0122] In some embodiments, in the step of stretching the second intermediate product, the transverse stretching temperature is 110°C-120°C, and can be 110°C-115°C; the longitudinal stretching temperature is 85°C-120°C, and can be 110°C-120°C. For example, in some embodiments, the transverse stretching temperature can be 110°C, 112°C, 114°C, 115°C, 116°C, 118°C, 120°C, etc., or a range consisting of any of the above values, for example, 110°C-114°C, 112°C-115°C, 115°C-118°C, 116°C-120°C, etc. In some embodiments, the longitudinal stretching temperature may be 85°C, 90°C, 95°C, 100°C, 104°C, 110°C, 115°C, 120°C, etc., or a range of any of the above values, for example, 85°C-90°C, 90°C-104°C, 100°C-115°C, 115°C-120°C, etc. In the step of stretching the second intermediate product, the transverse stretching temperature and the longitudinal stretching temperature are limited within the above ranges, so that the formed isolation film has better performance.

[0123] [Positive electrode]

[0124] In a secondary battery, a positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0125] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil.

[0126] There is no limitation on the specific type of the positive electrode active material. Any active material known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can select the active material according to actual needs.

[0127] As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates of olivine structure and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds. Examples of lithium-containing phosphates of olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their modified compounds. These materials can all be obtained commercially.

[0128] The modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.

[0129] The positive electrode film layer usually optionally includes a binder, a conductive agent and other optional auxiliary agents.

[0130] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive carbon black (Super P, SP), graphene and carbon nanofibers.

[0131] As an example, the binder can be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0132] [Negative electrode]

[0133] In a secondary battery, a negative electrode plate generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0134] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.

[0135] The specific type of negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of a secondary battery can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include, but is not limited to, one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. Silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained commercially.

[0136] In some embodiments, to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.

[0137] The negative electrode film layer usually optionally includes a binder, a conductive agent and other optional auxiliary agents.

[0138] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0139] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0140] As an example, other optional auxiliary agents may be thickening and dispersing agents (e.g. sodium carboxymethyl cellulose

[0141] Carboxymethylcellulose Sodium, CMC-Na), PTC thermistor materials.

[0142] [Electrolyte]

[0143] The secondary battery may include an electrolyte that conducts ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.

[0144] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0145] As an example, the solvent may be selected from ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), butylene carbonate (BC), butylene carbonate (BC), butylene carbonate (BC), butylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), butylene carbonate (BC), butylene carbonate (BC), butylene carbonate (FEC), butylene carbonate (MF), butylene carbonate ( One or more of propyl propionate (EP), propyl propionate (n-PropylPropionate, PP), methyl butyrate (Methyl ButyrateMB), ethyl butyrate (Ethyl Butyrate, EB), 1,4-butyrolactone (1,4-Butyrolactone, GBL), tetramethylene sulfone (SF), dimethyl sulfone (MethylSulfone, MSM), methyl ethyl sulfone (Methyl Ethyl Sulfone, EMS) and diethyl sulfone (Diethyl Sulfone, ESE).

[0146] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0147] In some embodiments, the secondary battery may be a lithium ion secondary battery. When the porous coating 13 is located between the first porous base film 11 and the second porous base film 12, the binder 14 can not only play a role in bonding the first porous base film 11 and the first porous base film 12, but also at least a portion of the filling particles 15 are embedded in the first porous base film 11 and / or the second porous base film 12 to a depth greater than or equal to 1 μm, thereby increasing the bonding force between the porous coating 13 and the first porous base film 11 and the second porous base film 12, thereby improving the reliability of the secondary battery.

[0148] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.

[0149] In some embodiments, the secondary battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0150] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0151] In some embodiments, reference Figure 5 The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity.

[0152] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator 10, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator 10, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying. After vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0153] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0154] The battery module 4 may further include a housing having a housing space in which the plurality of secondary batteries 5 are housed.

[0155] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0156] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0157] [Device]

[0158] The present application also provides an electrical device, which includes the secondary battery of the present application. The battery cell, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck), an electric train, a ship and a satellite, and an energy storage system.

[0159] The device can select battery cells, battery modules or battery packs according to its usage requirements.

[0160] Figure 7 The power consumption device 6 is taken as an example. The power consumption device 6 may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device 6's requirements for high power and high energy density of the secondary battery, a battery pack or a battery module may be used.

[0161] As another example, the electric device 6 may be a mobile phone, a tablet computer, or a notebook computer. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0162] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.

[0163] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0164] 1. Preparation of isolation membrane

[0165] Example 1

[0166] A polyethylene raw material with a crystallization temperature of 127°C, a polypropylene raw material with a crystallization temperature of 114°C, and a nucleating agent of calcium carbonate are provided, and a precursor is formed by mixing. The precursor is extruded and then cast into sheets. The temperature value of the first temperature stage is 135°C, and the temperature value of the second temperature stage is 120°C and stretched.

[0167] The preparation processes of Examples 2-16 and Comparative Examples 1-2 are similar, except that the raw material composition, nucleating agent, and casting sheet are adjusted. Please refer to Table 1.

[0168] 2. For the isolation membrane performance test, please refer to Table 2.

[0169] (1) Closed-cell temperature

[0170] 1. Sample preparation: cut the isolation film samples into a shape of 50mm*100mm, with at least 20 pieces per group.

[0171] 2. Test: Put the sample into an oven and heat it from room temperature to 110°C, then take it out for air permeability test. Perform air permeability test every time the temperature rises by 1°C, record the curve of air permeability changing with temperature, and record the temperature point where the air permeability changes suddenly as the closed-cell temperature.

[0172] (2) Closure time

[0173] 1. Sample preparation: cut the isolation film samples into a shape of 50mm*100mm, with at least 20 pieces per group.

[0174] 2. Test: Put the sample into an oven and heat it from room temperature to the closed-cell temperature, then take it out at regular intervals for air permeability test, record the air permeability change curve over time, and the time point of sudden change of air permeability is recorded as the closed-cell time.

[0175]

[0176]

[0177]

[0178] As can be seen from Table 1, compared with Comparative Examples 1-2, Examples 1-16 meet the requirement that the porous base membrane includes a matrix phase and a filling phase dispersed in the matrix phase, and the test curve of the differential scanning calorimeter of the porous base membrane includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase; therefore, the performance data of Examples 1-16 need to be better than those of Comparative Examples 1-2.

[0179] Comparing Example 1-2 with Example 3-9, it is shown that when the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is greater than 1, the performance data of Example 3-9 should be better than those of Example 1-2.

[0180] Compared with Examples 5-8, Examples 1-4 and 9 show that when the ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is 1.2-2.0, the performance data of Examples 1-4 and 9 should be better than those of Examples 5-8.

[0181] Compared with Examples 10 and 11, Examples 6, 7 and 12 show that when the porous base film has a diffraction peak in the range of 15°<2θ<17°, the performance data of Examples 6, 7 and 12 should be better than those of Examples 10 and 11.

[0182] Compared with Example 11, Examples 6, 7, 10, and 12 show that when the porous base membrane has a diffraction peak in the range of 23°<2θ<25°, the performance data of Examples 6, 7, 10, and 12 need to be better than that of Example 11.

[0183] Compared with Examples 10-12, Examples 6 and 7 show that the porous base membrane includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base membrane includes a second diffraction peak in the range of 23°<2θ<25°. When the diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak, the performance data of Examples 6 and 7 are better than those of Examples 10-12.

[0184] In summary, the isolation membrane provided in the embodiment of the present application includes a porous base membrane, and the porous base membrane includes a matrix phase and a filling phase dispersed in the matrix phase. The test curve of the differential scanning calorimeter of the porous base membrane includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase. The temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase, that is, the matrix phase has better thermal stability than the filling phase. Therefore, when the internal temperature of the secondary battery is high, the filling phase melts first due to its poorer thermal stability, thereby timely closing the pores of the isolation membrane, terminating the electrochemical reaction, and preventing the internal temperature of the secondary battery from continuing to rise, thereby improving the reliability of the secondary battery.

[0185] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. An isolation membrane, comprising a porous base membrane, wherein the porous base membrane comprises a matrix phase and a filling phase dispersed in the matrix phase, wherein a test curve of a differential scanning calorimeter of the porous base membrane includes both a melting peak of the matrix phase and a melting peak of the filling phase, and a temperature of the melting peak of the matrix phase is higher than a temperature of the melting peak of the filling phase.

2. The isolation film according to claim 1, characterized in that The ratio of the peak area of ​​the melting peak of the matrix phase to the peak area of ​​the melting peak of the filling phase is greater than 1, and can be selected to be 1.2-2.

0.

3. The isolation film according to claim 1 or 2, characterized in that: In the X-ray diffraction spectrum of the porous base film, the porous base film has a diffraction peak in the range of 15°<2θ<17°.

4. The isolation film according to any one of claims 1 to 3, characterized in that: In the X-ray diffraction spectrum of the porous base film, the porous base film has a diffraction peak in the range of 23°<2θ<25°.

5. The isolation film according to any one of claims 1 to 4, characterized in that: In the X-ray diffraction pattern of the porous base membrane, the porous base membrane includes a first diffraction peak in the range of 15°<2θ<17°, and the porous base membrane includes a second diffraction peak in the range of 23°<2θ<25°, and the diffraction peak intensity of the first diffraction peak is greater than the diffraction peak intensity of the second diffraction peak.

6. The isolation film according to any one of claims 1 to 5, characterized in that: The filling phase includes α-crystalline grains; and / or, The base film phase includes β-crystalline grains.

7. The isolation film according to any one of claims 1 to 6, characterized in that: The grain size of the filling phase is 0.1 μm-2 μm, and can be optionally 0.1 μm-0.5 μm.

8. The isolation film according to any one of claims 1 to 7, characterized in that: The mass proportion of the filling phase in the substrate is 10%-40%, and can be optionally 15%-25%.

9. The isolation film according to any one of claims 1 to 8, characterized in that: The relative molecular mass of the material of the filling phase is less than or equal to 1.2 million, and can be selected to be 400,000-600,000; and / or, The relative molecular mass of the material of the matrix phase is greater than or equal to 300,000, and can be selected from 300,000 to 2.5 million.

10. The isolation film according to any one of claims 1 to 9, characterized in that: The temperature of the melting peak of the matrix phase is 160°C-350°C, optionally 160°C-180°C; and / or, The temperature of the melting peak of the filling phase is 60°C-180°C, and can be optionally 80°C-130°C.

11. The isolation film according to any one of claims 1 to 10, characterized in that: The material of the matrix phase includes at least one of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polyetheretherketone, polyurethane, and polyester; and / or, The material of the filling phase includes at least one of polyethylene and polypropylene.

12. The isolation film according to any one of claims 1 to 11, characterized in that: The pore size of the porous base membrane is less than or equal to 0.5 μm, and can be selected to be 0.02 μm-0.1 μm.

13. The isolation film according to any one of claims 1 to 12, characterized in that: The isolation film satisfies at least one of the following (1) to (9): (1) The closed-cell temperature of the isolation film is 120°C-170°C, and can be 120°C-130°C; (2) The closure time of the isolation film is less than or equal to 10 seconds, and can be selected to be 5 seconds to 10 seconds; (3) The transverse elongation at break of the isolation film is ≥ 100%, and can be selected to be 100%-120%; (4) The longitudinal elongation at break of the isolation film is ≥ 60%, which can be 60%-80%; (5) The transverse tensile strength of the isolation film is ≥1500kgf / cm 2 , optional 2000kgf / cm 2 -4000kgf / cm 2 ; (6) The longitudinal tensile strength of the isolation film is ≥ 2000 kgf / cm 2 , optional 2000gf / cm 2 -4000kgf / cm 2 ; (7) The puncture strength of the isolation film is ≥ 60 gf, which can be selected from 120 gf to 420 gf; (8) The porosity of the isolation membrane is 30%-90%, and can be optionally 30%-50%; (9) The air permeability of the isolation membrane is less than or equal to 300 sec / 100 cc, and can be selected from 100 sec / 100 cc to 300 sec / 100 cc.

14. A method for preparing an isolation film according to any one of claims 1 to 13, characterized in that: include: Mixing a raw material for forming a matrix phase, a raw material for forming a filling phase, and a nucleating agent to form a precursor, wherein the crystallization temperature of the raw material for forming the filling phase is lower than the crystallization temperature of the raw material for forming the matrix phase; Extruding the precursor to form a first intermediate product; Performing a casting process on the first intermediate product to form a second intermediate product, wherein the casting process includes a first temperature stage and a second temperature stage, and the casting temperature of the first temperature stage is higher than the casting temperature of the second temperature stage; and Performing a stretching treatment on the second intermediate product to obtain a porous base film; The porous base membrane includes a matrix phase and a filling phase dispersed in the matrix phase. The test curve of the differential scanning calorimeter of the porous base membrane includes both the melting peak of the matrix phase and the melting peak of the filling phase, and the temperature of the melting peak of the matrix phase is higher than the temperature of the melting peak of the filling phase.

15. The method for preparing an isolation film according to claim 14, characterized in that: The melting index of the filling phase raw material is greater than the melting index of the matrix phase raw material; optionally, the ratio of the melting index of the filling phase raw material to the melting index of the matrix phase raw material is equal to 1.1-10.1, and can be optionally 1.1-2.

1.

16. The method for preparing a separator according to claim 14 or 15, characterized in that: The crystallization temperature of the filling phase raw material is 80°C-120°C, and can be optionally 80°C-100°C; And / or, the crystallization temperature of the matrix phase raw material is 125°C-135°C, optionally 125°C-130°C.

17. The method for preparing an isolation film according to any one of claims 14 to 16, characterized in that: The casting temperature in the first temperature stage is 125°C-135°C, and can be 125°C-130°C; and / or, The casting temperature in the second temperature stage is 105°C-125°C, and can be 105°C-110°C; and / or, The difference between the temperature of the casting piece in the first temperature stage and the temperature of the casting piece in the second temperature stage is 10°C-20°C.

18. The method for preparing an isolation film according to any one of claims 14 to 17, characterized in that: In the step of stretching the second intermediate product, the transverse stretching temperature is 110°C-120°C, optionally 110°C-115°C; and / or the longitudinal stretching temperature is 85°C-120°C, optionally 110°C-120°C.

19. A secondary battery, comprising an isolation membrane as described in any one of claims 1 to 13 or an isolation membrane prepared by the method for preparing an isolation membrane as described in any one of claims 14 to 18, wherein the secondary battery comprises a positive electrode sheet and a negative electrode sheet, and the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet.

20. An electric device comprising the secondary battery according to claim 19.

Citation Information

Patent Citations

  • Polypropylene double-way stretched film and preparation method thereof

    CN102139552A

  • Separator for lithium ion battery and its manufacturing method

    JP2009026499A

Cited By

  • Separator and preparation method therefor, secondary battery, and electric device

    EP4657643A1